Sex Differences Linking Pain-Related Fear and Interoceptive Hypervigilance: Attentional Biases to Conditioned Threat and Safety Signals in a Visceral Pain Model - Labrenz, Franziska; Knuf-Rtveliashvili, Sopiko; Elsenbruch, Sigrid (Frontiers in Psychiatry, 2020)
Although the broad role of fear and hypervigilance in conditions of the gut-brain axis like irritable bowel syndrome is supported by converging evidence, the underlying mechanisms remain incompletely understood. Even in healthy individuals, it remains unclear how pain-related fear may contribute to pain-related attentional biases for acute visceral pain. Building on our classical fear conditioning work in a clinically relevant model of visceral pain, we herein elucidated pain-related attentional biases shaped by associative learning in healthy men and women, aiming to elucidate possible sex differences and the role of psychological traits. To this end, we compared the impact of differentially conditioned pain-predictive cues on attentional biases in healthy women and men. Sixty-four volunteers accomplished a visual dot-probe task and subsequently underwent pain-related fear conditioning where one visual cue (CS+) was contingently paired with a painful rectal distention (US) while another cue remained unpaired (CS-). During the following test phase, the dot-probe task was repeated to investigate changes in attentional biases in response to differentially valenced cues. While pain-related learning was comparable between groups, men revealed more pronounced attentional engagement with the CS+ and CS- whereas women demonstrated stronger difficulties to disengage from the CS+ when presented with a neutral cue. However, when both CS+ and CS- were presented together, women revealed stronger difficulties to disengage from the CS-. Regression analyses revealed an interaction of sex, with negative affect predicting stronger avoidance of the CS+ and stronger difficulties to disengage attention from the CS- in men. These results provide first evidence that pain-related fear conditioning may induce attentional biases differentially in healthy women and men. Hence, sex differences may play a role in attentional mechanisms underlying hypervigilance, and may be modulated by psychological vulnerability factors relevant to chronic visceral pain.